Modification of ferromagnetic nanostripe dynamic behavior by edge defects. (30th March 2018) - Hu, Bo; Zhao, Chunwang; Li, Yulian
Abstract: The dynamic spectra of ferromagnetic nanostripes with different edge defects are investigated using the three-dimensional object-oriented micromagnetic framework code. Two main resonance peaks are found in nanostripes due to nonuniformity of the static magnetization patterns. The higher peak can be identified by the precession of magnetization in the middle part of the nanostripes. The lower one can be identified by the sample end part. The values of two precession frequencies and linewidths can be modified using the edge defect to tune the magnetization of different parts of samples, which is important and useful in magnetic storage devices.